Sex‐ and age‐related differences in kinetics and tibial accelerations during military‐relevant movement tasks in U.S. Army trainees. - Johnson, Caleb D.; Sara, Lauren K.; Bradach, Molly M.; Zeppetelli, David J.; Dæhlin, Torstein E.; Mullineaux, David R.; Foulis, Stephen A.; Hughes, Julie M.; Davis, Irene S. (European Journal of Sport Science, 2024)
Lower extremity injuries are prevalent in military trainees, especially in female and older trainees. Modifiable factors that lead to higher injury risk in these subgroups are not clear. The purpose of this study was to identify whether external loading variables during military‐relevant tasks differ by age and sex in U.S. Army trainees. Data was collected on 915 trainees in the first week of Basic Combat Training. Participants performed running and ruck marching (walking with 18.1 kg pack) on a treadmill, as well as double‐/single‐leg drop landings. Variables included: vertical force loading rates, vertical stiffness, first peak vertical forces, peak vertical and resultant tibial accelerations. Comparisons were made between sexes and age groups (young, ≤19 years; middle, 20–24 years; older, ≥25 years). Significant main effects of sex were found, with females showing higher vertical loading rates during ruck marching, and peak tibial accelerations during running and ruck marching (p ≤ 0.03). Males showed higher vertical stiffness during running and peak vertical tibial accelerations during drop landings (p < 0.01). A main effect of age was found for vertical loading rates during running (p = 0.03), however no significant pairwise differences were found between age groups. These findings suggest that higher external loading may contribute to higher overall injury rates in female trainees. Further, higher stiffness during running may contribute to specific injuries, such as Achilles Tendinopathy, that are more prevalent in males. The lack of differences between age groups suggests that other factors contribute more to higher injury rates in older trainees. Highlights: Female trainees showed higher lower extremity loading during running and ruck marching that may predispose them to higher rates of musculoskeletal injury during initial‐entry training.Male trainees showed higher stiffness during running, which may relate to an increased risk of specific musculoskeletal injuries that are more prevalent in males, such as Achilles tendinopathy.Overall, older trainees did not show different lower extremity loading patterns compared to younger, suggesting that these factors are not related to the increased risk for musculoskeletal injury in older trainees.